PENGARUH DIMENSI KUALITAS LAYANAN TERHADAP TINGKAT KEPUASAN PELANGGAN SIM CARD KARTU HALO TELKOMSEL REGIONAL AMBON (UNIT PELAYANAN GRAPARI AMBON) - Meggy R Wattimena (FEB Universitas Sultan Ageng Tirtayasa, 2017)
This study aims to test and analyze the effect of service quality on the level of customer satisfaction, especially HALO card customers at the Telkomsel GraPARI service unit in Ambon.This research was conducted in Ambon City and the object of research at PT. Telkomsel Regional XI Sumalirja GraPARI service unit Ambon. The data collection process uses an estimation technique with a sample of 110 active customers. The data analysis technique uses multiple linear regression analysis.The results showed that tangible has a positive influence on HALO card customer satisfaction with a coefficient of 0.177, reliability has a positive influence on HALO card customer satisfaction with a coefficient of 0.163, responsiveness has a positive influence on HALO card customer satisfaction with a coefficient of 0.235, assurance has a positive effect to HALO card customer satisfaction with a coefficient of 0.240 and empathy has a positive effect on HALO card customer satisfaction with a coefficient of 0.182. The results of this study indicate that the dimensions of service quality are able to shape customer satisfaction of HALO cards